How to Encourage Employee Work Performance in Facing Construction Digitalization Transformation - Parluhutan, Bobby; Moeins, Anoesyirwan; Marhalinda (Dinasti Publisher, 2024)
organizational climate, organizational commitment, and readiness to change on the work performance of employees of PT Wijaya Karya Bangunan Gedung Tbk both partially and simultaneously. This research uses a descriptive and verifiable approach. The sample used was 235 respondents. Sampling applied non-probability sampling techniques, techniques with purposive sampling Data was distributed using a survey method with questionnaire instruments that had previously been tested for validity and reliability with SPSS software. The data analysis method used in this study is the Structural Equation Model (SEM). The analysis using SEM was carried out with the help of the Lisrel program. The results of the study show that partially, adaptive leadership and organizational climate have a positive and significant effect on readiness to change, but organizational commitment has a negative but not significant influence. Simultaneously adaptive leadership. Organizational climate and organizational commitment have a positive and significant effect on readiness to change. Both partially and simultaneously adaptive leadership, organizational climate, organizational commitment, and readiness to change have a significant effect on employee work performance. The results of the determination test were obtained by 55%.